Faktor Yang Mempengaruhi Earning Management Pada Perusahaan Manufaktur Yang Terdaftar Di BEI - Christoforus Richard, Agustin Ekadjaja (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this research is to analyze the effect of earning power, firm size and leverage on earning management. This research uses manufacturing industries listed in Indonesian Stock Exchange for the period 2014-2016 as the population. Purposive sampling technique was used and 115 were selected as samples. Data processing in this research used software program IBM SPSS version 23. The result shows that: (1) There is a significant impact of Earning power on Earning management. There are no significant impact of Firm size and Leverage on Earning management. (2) There is simultanously a significant impact of Earning power, Firm size, and Leverage on Earning management.